ISOLATION AND CHARACTERIZATION OF SECONDARY METABOLITE FROM HABENARIA INTERMEDIA D.DON FOR EVALUTION OF HEPATOPROTECITVE ACTIVITY AGAINST CARBON TETRACHLORIDE INDUCED LIVER DAMAGE IN ALBINO RATS - Goudar, Mahesh Anand; H, Jayadevappa; Km, Mahadevan; Ra, Shastry Ra4shastry; Pv, Habbu; Ha, Sayeswara (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Isolation and characterization of secondary metabolite from Habenaria intermedia D Don for assessment of hepatoprotecitve activity against carbon tetrachloride (CCl4) induced liver damage in albino rats. Methods: The phenolic constituents present in ethanolic fraction of tubers of H. intermedia was isolated by column chromatography using gradient elution technique. The isolated phenolic compound was characterized by infrared, 1H nuclear magnetic resonance and mass spectral analysis. The isolated compound was screened for hepatoprotecitve activity against liver toxicity induced in Albino rats by intraperitoneal injection of CCl4. Albino rats weighing 150-200 g were randomly divided in to four groups of six rats each. Group I served as normal control and received only 1% tween in distilled water. Group II served as a negative control and received CCl4 in liquid paraffin at the dose of 0.7 ml/kg.p.o. CCl4 on alternate days. Group III and IV were intoxicated with CCl4 0.7 ml/kg.p.o. before the administration of silymarin 100 mg/kg.p.o. and isolated phenolic constituent (gallic acid) in polyethylene glycol at the dose of 25 mg/kg.p.o. respectively. Various liver function biochemical parameters such as serum glutamic oxaloacetic transaminase (SGOT), serum glutamic-pyruvic transaminase (SGPT); serum bilirubin and total protein were assessed before and after treatment to investigate the hepatoprotecitve activity. Histopathology of liver sections of rats treated with isolated phenolic constituents was also studied. Results: It was observed that in CCl4 intoxicated group SGPT, SGOT, serum bilirubin levels were elevated, and the total protein content was decreased when compared to the control group. Administration of isolated phenolic constituent at the dose of 25 mg/kg.p.o. reduced these pathological damages caused by CCl4 intoxication compare to normal, and silymarin treated groups. The results were further supported by histopathology of isolated phenolic constituent treated rat liver, which showed the presence of normal hepatic cords, absence of necrosis and fatty infiltration. Conclusion: The present study has justified that the isolated phenolic constituent (gallic acid) exhibited significant hepatoprotecitve potential against CCl4 induced toxicity in Albino rats, thus enabling to expand the spectrum of novel hepatoprotecitve formulations. Keywords: Habenaria intermedia, Gallic acid, Hepatoprotecitve, Carbon tetrachloride toxicity, Silymarin.